ϕ-Approximate Biprojective and ϕ-Approximate Amenable Banach Algebras - Ghorbani, Zahra (Eurasian Mathematical Journal, 2022)
Let A be a Banach algebra and ϕ be a continuous homomorphism on A. We define the notions of a ϕ-approximate biprojective and ϕ-approximate amenable Banach algebra A, and consider relations between them and some their properties.